THE EFFECT OF PHENOMENES IN DİJİTAL MARKETİNG ON THE BUYING DECISION OF CONSUMERS AND BRAND LOYALTY: ISTANBUL PROVINCE UNIVERSTY STUDEN (Third Sector Social Economic Review, 2022)
Due to the expected frequency of use in social media in the future, many brands are trying to create brand awareness by promoting their services in social media as well as their products. Those who will do this are social media phenomena whose number of followers is constantly increasing and which is thought to affect their followers. In the digital world, the term phenomenon is mostly used to describe people who affect society on virtual platforms or social media. The phenomena, which are shown as the opinion leaders of digital marketing, are also in the lead role of a new marketing method. This method is called phenomenon marketing in the marketing literature. The aim of the research is to determine whether the trust in social media phenomena affects the brand loyalty process in digital marketing, which is accepted as a new marketing method, and to determine the effect of the followers on the purchasing decision process with the product promotion of the phenomena. For this purpose, T-test and ANOVA were used to determine the difference in purchasing and brand loyalty according to gender, age, education level, daily social media usage time, and the number of phenomena followed. SPSS 22 package program was used. The online questionnaire was applied to 398 volunteers from consumers studying in Istanbul and using social media. The data showed more credible phenomena that the respondents found candid and that could produce their own unique content. It was determined that the influence of the phenomena in brand awareness and not being significant according to age, and that the phenomena were more active in consumer purchasing than brand awareness.
Keywords: Digital Marketing; Phenomenon; Consumer; Purchase Decision; Brand Loyalty